The Effect of the Implementation of Sharia Management Functions on Employee Performance at Sharia Bank - Anang Satrus; Ahmad Afandi (Newinera Publisher, 2024)
The research focuses on the effects of sharia management function implementation towards the employee performance of PT BPRS Puduarta Insani Tembung an Islamic financial sharia banking company in Indonesia. The research therefore seeks to test the hypothesis that there is a correlation between Shariah compliant management practices that comprises of Planning, Organizing Actuating and controlling (POAC) and the performance of the employees. A quantitative research approach was therefore used, and questionnaires duly administered to all the twenty employees in the institution to capture all relevant responses. Data analysis was done using SPSS version 26; the primary analytical technique deployed here was simple linear regression analysis with the view of establishing the nature of the relationship between the variables. The results show that there exists a positive relationship between the Sharia management functions and the level of performance of the employees with management practices accounting for 74 percent. In its turn, personality explains 1% of the variance in performance outcomes. This implies that Sharia management practices are essential in the improvement of employee performance, because they not only proffer a working structural model, but also offer an organizational cultural solution to the improvement of organizational performance through deontological legal standards and then Islamic tenets. The outcomes of the study affirm the relevance of incorporating principles of Sharia in the management so as to create increased commitment, increased enthusiasm and higher employee performance in Islamic banks. The final implications for future research are proposed to look into organisational differences that may cause variations of these findings and possible moderator variables that may regulate this relationship.